Part One: Debunking Prevailing Scholarly Views Pertaining to the Apostasy of Alleged Descendants of Shaykh Yusuf of Makassar - Najma Moosa (Al-Jami'ah: Journal of Islamic Studies, 2020)
This article focuses on the controversial issue of apostasy pertaining to the alleged family of Shaykh Yusuf of Makassar, the Indonesian pioneer of Islam in colonial South Africa, after his demise at the Cape in the late 17th century during a period of Dutch occupation of both countries. It is reported in local and international historical and scholarly sources that the second generation grandchildren of this political exile and learned Islamic scholar converted from Islam to Christianity at the Cape and thereafter entered into marriages with Christian spouses. Their mother is alleged to have been the Shaykh’s daughter, Zytie Sara Marouff (alias Care Sale), and their father, the Rajah or King of Tambora (alias Abulbasi Sultan), a fellow exiled countryman. The marriage between the Rajah and Zytie is alleged to have taken place shortly after his arrival at the Cape in 1698 but before the death of Shaykh Yusuf in 1699. The conversions are recorded to have taken place within two decades of the Shaykh’s death and shortly after the death of their father, the Rajah, in 1719; both averted death sentences but died during exile at the Cape. The main aim of this article is to critically analyse these sources, which contain both conflicting information, and whose authors express ambivalent views, in an attempt to unravel the mystery surrounding their conversion and the marriage of their parents. Although some local Muslim religious authorities (ulama) at the Cape are aware of these conversions, many are not. In fact, these conversions were overlooked in a publication on the very topic. Local Muslims have therefore not been fully apprised by them of this aspect of their history because the topic is understandably also a sensitive one. The aim of this article is therefore not to dispute these facts or even that these conversions may have been a voluntary exercise and a consequence of freedom of choice. Although an analysis of some of the policies of the then Dutch colonial government which were enforced at the Cape (for example, those pertaining to interracial and interreligious marriages amidst limited religious freedom) are referred to, this article highlights that socio-economic reasons (poverty) and practical expediency (marriage) may indeed have precipitated such conversions. A detailed critical analysis, including of the Islamic law (Shari’a) pertaining to freedom of religion and apostasy, is unfortunately beyond the scope of this article due to space constraints. [Artikel ini membahas kontroversi pindah agama pada keluarga Syekh Yusus Makassar selepas diasingkan di Afrika Selatan pada masa kolonial Belanda akhir abad 17. Menurut sumber lokal dan tulisan sarjana internasional menyatakan bahwa generasi kedua keturunan Syekh Yusuf telah memeluk Kristen serta menikah dengan pasangan Kristen. Cucu yang dimaksud adalah anak dari putri Syekh Yusuf, Zytie Sara Marouff, yang menikah dengan Raja Tambora yang juga ikut dalam pengasingan di Cape Town. Pernikahan itu diperkirakan terjadi setelah rombongan tiba di Cape Town tahun 1698 dan sebelum wafatnya Syekh Yusuf tahun 1699. Sedangkan konversi agama yang terjadi sekitar dua dekade setelah wafatnya Syekh Yusuf dan selepas wafat ayah mereka Raja Tambora tahun 1719. Fokus utama artikel ini adalah mengkritisi sumber-sumber informasi yang bertentangan dan pandangan-pandangan para penulis yang ambivalen dalam rangka memperjelas misteri mengenai konversi dan pernikahan kedua orang tua mereka. Walaupun ulama lokal di Cape Town menyadari tentang konversi tersebut, namun sebagian besar tidak memperdulikannya. Sayangnya konversi ini dilihat berlebihan dalam berbagai tulisan. Lagipula penduduk muslim setempat tidak menjelaskan informasi hal ini pada catatan sejarah mereka karena dipahami sebagai hal yang sensitif. Oleh karena itu, artikel ini tidak bermaksud untuk memperdebatkan atau bahkan menguji fakta mengenai konversi agama yang memang bagian dari hak kebebasan beragama. Walaupun artikel membahas pelaksanaan kebijakan kolonial Belanda (misal pembatasan pernikahan antar ras dan antar agama ditengah pembatasan kebebasan beragama), artikel ini juga membahas sekilas soal kemiskinan dan praktik kebijaksanaan pernikahan dalam mengendapkan persoalan konversi. Namun karena keterbatasan halaman maka artikel ini tidak membahas persoalan hukum Islam mengenai kebebasan beragama dan pindah agama.]